Contest carnage! - Cole, Stephen; Fox, Woody (Red Fox London, 2008)
Teggs and his friends are going to be the youngest contestants in the Megasaur challenge! Robot-Boxing, Rock Tennis and Weight Lifting mean the Daring Dinos can show that they really are the best, strongest and bravest Astro-cadets. But the Megasaur challenge turns out to be mega-unlucky and lots of contestants keep getting 'accidentally' hurt. Will Teggs and his friends be hurt, too? Or will they discover who's behind all the problems at the contest before it's too late?